2001
DOI: 10.1029/2000jd900734
|View full text |Cite
|
Sign up to set email alerts
|

Saharan dust profiles measured by lidar at Lampedusa

Abstract: In the upper region, large aerosol concentrations last for a few days; during these events aerosol is often detected up to 7 or 8 kin. Large amounts were detected in mid-May and were very often observed in June. By using meteorological analyses and isentropic backward trajectories, the aerosol behavior above Lampedusa has been related to the large-scale transport patterns and to the source regions. Large aerosol loads are clearly due to dust transport from Africa, occurring through two main paths: from central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
0
8

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(96 citation statements)
references
References 42 publications
(5 reference statements)
3
84
0
8
Order By: Relevance
“…They found that the largest values of α correspond to airmasses coming from Eastern Europe and Russia. The aerosol origin sector can be identified by considering the time spent in the different sectors along the trajectory (di Sarra et al, 2001;Gerasopoulos et al, 2003), or by more sophisticated correlation methodologies (Formenti et al, 2001). Previous results (di Sarra et al, 2001), as well as a preliminary analyses of this dataset, indicate that dust is loaded in the air column even after a marginal passage over the African continent.…”
Section: Identification Of the Aerosol Originmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the largest values of α correspond to airmasses coming from Eastern Europe and Russia. The aerosol origin sector can be identified by considering the time spent in the different sectors along the trajectory (di Sarra et al, 2001;Gerasopoulos et al, 2003), or by more sophisticated correlation methodologies (Formenti et al, 2001). Previous results (di Sarra et al, 2001), as well as a preliminary analyses of this dataset, indicate that dust is loaded in the air column even after a marginal passage over the African continent.…”
Section: Identification Of the Aerosol Originmentioning
confidence: 99%
“…In this study we use trajectories that end over Lampedusa at 750, 2000, and 4000 m. Previous investigations based on spring-summer lidar observations (di Sarra et al, 2001) and model results (e.g. Alpert et al, 2004) have shown that African airmasses are generally loaded with desert dust up to at least 4 km, and often up to 7-8 km.…”
Section: Identification Of the Aerosol Originmentioning
confidence: 99%
“…The first two years of regular observations by the EARLINET stations showed frequent transport of Saharan dust from southern Europe to central and northern Europe. It has been shown that dust plumes may be found in heights well above the surface [Hamonou et al, 1999;Gobbi et al, 2000;Di Sarra et al, 2001;Mattis et al, 2002b;Welton et al, 2000]. Observations of mineral dust in different parts of the Mediterranean region revealed significantly different optical properties, as the result of highly variable physical and chemical properties [e.g., Sokolik et al, 1998;von Hoyningen-Huene et al, 1999;Tanré et al, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…A challenge in the creation of an adequate data set was the adjustment between optical measurements made through the total atmospheric column and aerosol sampling at ground level. Representativeness of surface sampling for dust events is problematic due to the fact that dust maybe transported at high altitudes (Hamonou et al, 1999;di Sarra et al, 2001;Tsidulko et al, 2002;Dulac and Chazette, 2003;Alpert et al, 2004) and not be adequately sampled at the surface. An additional problem is that the aerosolsampling unit collects particles during two or three days on one filter, thus it may contain particles from different events and sources.…”
Section: Data Integrationmentioning
confidence: 99%